2010
DOI: 10.1111/j.1365-2966.2010.17575.x
|View full text |Cite
|
Sign up to set email alerts
|

A high-velocity narrow absorption line outflow in the quasar J212329.46 − 005052.9

Abstract: We report on the discovery of a high-velocity narrow absorption line outflow in the redshift 2.3 quasar J212329.46 − 005052.9. Five distinct outflow systems are detected with velocity shifts from −9710 to −14 050 km s −1 and C IV λλ1548, 1551 linewidths of FWHM ≈ 62-164 km s −1 . This outflow is remarkable for having high speeds and a degree of ionization similar to broad absorption line (BAL) flows, but linewidths roughly 100 times narrower than BALs and no apparent X-ray absorption. This is also, to our know… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
127
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 101 publications
(153 reference statements)
20
127
1
Order By: Relevance
“…In contrast to the rare situations where partial covering occurs from intervening systems (see also Petitjean et al 2000), partial covering is typical for absorption systems associated with quasars ( e.g. Petitjean et al 1994;Rupke et al 2005;Hamann et al 2010;Muzahid et al 2013). A failure to take into account the partial coverage effect in a spectroscopic analysis can lead to a significant underestimation of the column density of an absorber.…”
Section: Effect Of Partial Coveringmentioning
confidence: 95%
“…In contrast to the rare situations where partial covering occurs from intervening systems (see also Petitjean et al 2000), partial covering is typical for absorption systems associated with quasars ( e.g. Petitjean et al 1994;Rupke et al 2005;Hamann et al 2010;Muzahid et al 2013). A failure to take into account the partial coverage effect in a spectroscopic analysis can lead to a significant underestimation of the column density of an absorber.…”
Section: Effect Of Partial Coveringmentioning
confidence: 95%
“…The tail may represent a BALQ population with a non-saturated C iv absorption (τ ∼ 1), which is expected to be larger for a harder SED that can overionize larger columns of gas. Alternatively, the observed CF may be produced by the projected area of inhomogeneous gas clumps with τ ≫ 1 (Hamann et al 2011). This area decreases for a harder SED, as the outer parts of the clumps become overionized, producing the observed tail of small values of CF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to distinguish intrinsic NALs from intervening and associated absorption lines in the same spectrum, especially in low or moderate resolution spectra. Many previous studies have revealed that intrinsic absorption lines can vary in equivalent width over timescales of months to years (e.g., Wise et al 2004;Narayanan et al 2004;Gibson et al 2008Gibson et al , 2010Hamann et al 2011;Hacker et al 2013;Chen & Qin 2013;Misawa et al 2014). The line variability is a good indicator to determine whether NALs are truly intrinsic to quasars or not.…”
Section: Introductionmentioning
confidence: 99%